HISTÓRIA CULTURAL E A CONTRIBUIÇÃO DE ROGER CHARTIER - José D’Assunção Barros (Dialogos, 2018)
Resumo. Este artigo busca esclarecer e discutir alguns aspectos relacionados à modalidade da História Cultural, enfatizando mais especificamente a perspectiva da História Cultural proposta por Roger Chartier. Discute, ainda, diversos dos conceitos envolvidos na perspectiva de História Cultural. O artigo remete a uma obra recentemente publicada pelo autor deste texto, cujo principal objetivo é o de elaborar uma visão panorâmica das diversas modalidades da História nos dias de hoje. Abstract. This article attempts to clarify and discuss some aspects related to the modality of Cultural History, emphasizing the perspective of Cultural History of Roger Chartier, and discussing various concepts concerning the Cultural History. The article refers to a recently publicized work of the author of this text, witch principal subject was to elaborate a panoramic view of the various fields in which ones the historical knowledge is divided nowadays.